Direct comparison of β-glucan content in wild and cultivated barley. Issue 1 (1st January 2018) - Nishantha, Mutthanthirige Don Lalith Chandana; Zhao, Xian; Jeewani, Diddugodage Chamila; Bian, Jianxin; Nie, Xiaojun; Weining, Song
ABSTRACT: β-Glucan is an important chemical found in cereals, tremendously beneficial to human health. In this study, β-glucan contents in wild and cultivated barley from representative regions worldwide were investigated. Results exhibited that coeﬃcient of variation of β-glucan content of wild and cultivated barley was 24.18% and 13.99%, respectively. The β-glucan contents of studied wild barley accessions were ranged from 3.26% to 7.67% while cultivated barley varieties were ranged from 2.68% to 4.74%. A significant difference of β-glucan content ( p  ≤ 0.001) was found between wild and cultivated barely. Wild barley showed a higher β-glucan content and variation than cultivated barley. This study gives an idea about elite germplasms for genetic improvement and shed light to trace barley domestication in relation to grain metabolite view.